Care for Animal Rights in Islam - Sarwar, Muhammad; Raza, Ahmed; Tanzeem, Hafiz Muhammad (Al-Irfan, 2021)
The research article, “Care for Animal Rights in Islam” deals with the rights, Islam has granted to animal kingdom. The formal history of the animal rights does not date back to hundreds of years. Today human research has reached its apex, but the animal rights are not being handled fairly. Some societies got extreme on this score in that animals may receive greater attention compared to humans. On the other hand, some nations are stingy with the care and welfare of dumb creatures. As per the Scriptural verdict, Allah sent Adam – the first human being to the world as His vicegerent. They are the signs of the Creator’s dignity and sagacity. They have communities of their own. The Qur’an says Allah inspires both humans and animals. Animals deserve extra special attention in that they cannot verbalize their pains where as humans not only claim but also exact them. Islam gives license to humans to make use of animal kingdom, provided that they do not lead them with more burden than they can bear, are well fed and watered and properly cared. They must be nursed back to health.